Application of Information Motivation Behavior Skill Model on Maternal Parenting Behavior on Child Growth in Sleman, Yogyakarta, Indonesia - Agustin Mahardika Hariyadi; Eti Poncorini Pamungkasari; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Toddler growth disorders in Indonesia reach 59% of the highest ranking in the ASEAN continent, including: physical growth disorders, motor development, language and behavior. Suboptimal child growth can be avoided if mothers are able to support toddler growth by providing the right parenting pattern. Proper parenting can optimize child growth and development. This maternal behavior can be done by applying the Information Motivation Behavior (IMB) skill model. The purpose of this study aims to explore the application of the IMB model-based application to maternal parenting behavior on child growth in Sleman Regency. Subjects and Method: This was a cross-sectional study was conducted at 25 integrated health posts (Posyandu) in Sleman Regency, Yogyakarta, in April-May 2024. A sample of 200 mothers who have toddlers aged 24-60 months was selected using the stratified random sampling. The dependent variable was child growth. The independent variables were information, motivation, skills, and maternal parenting behavior. Data collection was using questionnaires and data analysis was using path analysis with Stata 13. Results: Maternal parenting behavior increased with good behavioral skills (OR = 1.28; 95% CI 0.60 to 1.97; p <0.001), good information (OR = 1.20; 95% CI 0.52 to 1.88; p <0.001), and strong motivation (OR= 0.98; 95% CI= 0.31 to 1.66; p= 0.004). Toddler growth is positively influenced by maternal parenting behavior (OR= 1.29; 95% CI= 0.46 to 2.13; p= 0.002) and family income (OR = 3.15; 95% CI = 1.92 to 4.38; p <0.001). Conclusion: Maternal parenting behavior increases with good behavioral skills, good information and strong motivation. Toddler growth is positively influenced by maternal parenting behavior and family income.